Pharmacy education in the twenty first century and beyond : global achievements and challenges - Fathelrahman, Ahmed Ibrahim; Mohamed Izham Mohamed Ibrahim; Alrasheedy, Alian A.; Wertheimer, Albert I. (Academic Press, an imprint of Elsevier, 2018)
Pharmacy Education in the Twenty First Century and Beyond: Global Achievements and Challenges offers a complete reference on global pharmacy education, along with a detailed discussion of future issues and solutions. This book begins with a brief overview of the history of pharmacy education, covering all levels of education and styles of learning, from undergraduate, continuing professional education, and methods for self-learning and development. Teaching strategies such as team-based learning, problem-based learning and interdisciplinary education are also described and compared to conclude why certain pharmacy programs attract students, and why educators prefer particular teaching strategies, assessment tools and learning styles. As a result, this book provides pharmacy educators, administrators, students and practitioners with a comprehensive guide to pharmacy education that will enable readers to choose the best approaches to improve, reform or select a program based on worldwide experience and the latest available evidence and research.